A Comparison of Azathioprine and Mycophenolate Mofetil as Adjuvant Drugs in Patients with Pemphigus: A Retrospective Cohort Study - Siriorn Sukanjanapong; Darin Thongtan; Silada Kanokrungsee; Poonkiat Suchonwanit; Kumutnart Chanprapaph (Adis, Springer Healthcare, 2019)
Abstract Introduction Azathioprine (AZA) and mycophenolate mofetil (MMF) are both first-line steroid-sparing agents used for the treatment of pemphigus in combination with a corticosteroid, but few studies to date have directly compared these two combination treatment modalities. The aim of this study was to compare the efficacy and safety of each of these agents as adjuvant therapy with the corticosteroid prednisolone for the treatment of pemphigus, using standardized outcome parameters. Methods This was a retrospective study of patients with pemphigus who received corticosteroid therapy in combination with either AZA or MMF at the Autoimmune Blistering Skin Diseases Clinic of Ramathibodi Hospital (Bangkok) between January 2007 and July 2017. The treatment response was evaluated using early [end of the consolidation phase (ECP)] and late endpoints [complete remission (CR) on therapy, CR off therapy and immunological remission]. Cumulative steroid use, relapse rate and adverse events in each treatment group were also compared. Results Of the 62 patients with pemphigus included in the study, 37 were treated with prednisolone plus AZA as adjuvant (AZA group) and 25 patients were treated with prednisolone plus MMF as adjuvant (MMF group). The majority of patients in both treatment groups reached the ECP (AZA group 88.2%; MMF group 71.4%; between-group difference not statistically significant at p = 0.156); the median time required to achieve this early endpoint was also comparable (p = 0.362). A high percentage of patients in both the AZA and MMF groups attained CR on therapy (AZA 73%; MMF 72%). The total number of patients who achieved CR on and off therapy were comparable in the two groups (p = 0.933 and p = 0.690, respectively). However, the median time for patients to achieve CR on therapy was significantly shorter for those on MMF than for those on AZA (7.3 vs. 12.5 months; p = 0.019), and the cumulative steroid dose required for patients to achieve CR both on and off therapy was significantly lower in the MMF group than in the AZA group (p = 0.007 and p = 0.043, respectively). Conclusion While corticosteroid in combination with either AZA or MMF is an effective therapeutic regimen for the treatment of pemphigus, MMF demonstrates a shorter time to achieve CR on therapy and has a significantly higher steroid-sparing effect.